2021
DOI: 10.2139/ssrn.3795497
|View full text |Cite
|
Sign up to set email alerts
|

Parental Decision and Intent Towards COVID-19 Vaccination in Children With Asthma. An Econometric Analysis

Abstract: Objective. Vaccination will be instrumental in controlling the COVID-19 pandemic, and vaccination of children will be necessary to achieve herd immunity. Given that children with chronic health conditions may be at increased risk of COVID-19, it is crucial to understand factors in uencing parental decisions about whether to have their child vaccinated. The study objectives were to measure parental intent to have their child with asthma vaccinated against COVID-19 and identify the determinants of their vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 45 publications
1
13
1
2
Order By: Relevance
“…In the months shortly following the FDA’s EUA of the first COVID-19 vaccine for adults (early 2021), less than one-half of parents of children with T1D in this study reported “everyone” in the family, including children, intended to receive the COVID-19 vaccine. This contrasts with data from a pediatric asthma sample in Canada (conducted August, 2020) and a general, international sample (conducted March to May, 2020), which reported approximately two-thirds of parents endorsed vaccination intentions ( Drouin et al, 2021 ; Goldman et al, 2020 ). These differences may be due to younger child age, which is a predictor of lower parent COVID-19 vaccination intention ( Goldman et al, 2020 ) and defining characteristics of this sample.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In the months shortly following the FDA’s EUA of the first COVID-19 vaccine for adults (early 2021), less than one-half of parents of children with T1D in this study reported “everyone” in the family, including children, intended to receive the COVID-19 vaccine. This contrasts with data from a pediatric asthma sample in Canada (conducted August, 2020) and a general, international sample (conducted March to May, 2020), which reported approximately two-thirds of parents endorsed vaccination intentions ( Drouin et al, 2021 ; Goldman et al, 2020 ). These differences may be due to younger child age, which is a predictor of lower parent COVID-19 vaccination intention ( Goldman et al, 2020 ) and defining characteristics of this sample.…”
Section: Discussioncontrasting
confidence: 64%
“…Clinically, vaccine recommendations from pediatric healthcare and mental health providers may have an important role on parent COVID-19 vaccine intention, especially for some parents of children with T1D who experience uncertainty about the COVID-19 vaccine due to difficulty identifying trustworthy information sources. The only other reported study of parent COVID-19 vaccination intention in a pediatric chronic illness sample found that contact with a healthcare professional increased intention ( Drouin et al, 2021 ). Briefly assessing parent perceptions of the trustworthiness of their information sources could identify families most likely to benefit from professional recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination will be instrumental in controlling the COVID-19 pandemic, and vaccination of a patient with a chronic illness will be necessary as they were amongst the increased risk of COVID-19. Large-scale vaccination efforts will be required, and governments worldwide are currently devising vaccination strategies ( Drouin et al, 2021 , Lazarus et al, 2021 ). One key element of any strategy is the acceptance of the vaccine by the general public.…”
Section: Introductionmentioning
confidence: 99%
“…Puisque les vaccins contre la COVID-19 commencent à être approuvés pour les enfants, les résultats font ressortir la nécessité de planifier des interventions communautaires ciblées pour réduire la transmission communautaire et accroître le taux de vaccination. Compte tenu du taux estimatif de 25 % des parents québécois d’enfants de moins de 12 ans qui expriment leur refus à faire vacciner leur enfant, ces efforts pourraient être particulièrement requis dans les quartiers où la défavorisation matérielle est plus marquée ( 26 , 27 ). Ce peut être une tâche difficile, puisque ces caractéristiques sociodémographiques sont liées à une plus faible intention de se faire vacciner contre la COVID-19 ( 26 , 28–31 ).…”
Section: Exposéunclassified